Strategi Berbasis Nabawiyyah untuk Pembelajaran Aqidah Anak di Sekolah Islam - Atma Mahendra, Arif; Khairi, Burhanudin; Defriyadi, Defriyadi; Kholid, Idham; Ghazi, Fachrul; Erlina, Erlina (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2026)
This study aims to analyze strategies for teaching aqeedah to children in Islamic schools by emphasizing the Nabawiyyah model as a pedagogical foundation for faith and spiritual formation. The main question addressed concerns how a prophetic-based approach can be integrated into aqeedah learning to move beyond cognitive domains toward affective and practical dimensions. Conceptually, this study positions itself as a framework proposing an aqeedah learning approach rooted in the Prophet’s exemplary model (uswah hasanah). The research employed a critical literature review of classical Islamic education sources, contemporary studies, and Islamic curriculum documents. Content analysis was applied to identify strategic elements of prophetic learning, including role modeling, value internalization, and habituation aligned with children’s psychological development. The findings reveal that Nabawiyyah-based strategies effectively strengthen students’ faith and morality through modeling, prophetic narratives, and religious habituation. The study concludes that this approach provides a holistic conceptual framework for aqeedah education in madrasahs and offers a pedagogical response to the moral crisis of the digital era.